Albania’s Energy Sector : Vulnerable to Climate Change - Ebinger, Jane (World Bank, Washington, DC, 2012)
Energy security is a critical concern in Albania which relies on hydropower for about 90 percent of its electricity production. While renewable energy resources like hydropower play a fundamental role in moving the world towards a low-carbon economy, they can also be vulnerable to climatic conditions. This Knowledge Brief provides an overview of a pilot vulnerability, risk, and adaptation assessment undertaken for Albania's energy sector by the Energy Sector Management Assistance Program (ESMAP), the World Bank and the Trust Fund for Environmentally and Socially Sustainable Development (TFESSD), in partnership with stakeholders in Albania's energy sector. The assessment raised awareness and initiated dialogue on energy sector adaptation. It was aimed at building greater understanding of the climate risks faced by the energy sector and of priority actions that could be taken to reduce vulnerabilities.